Design, Preparation and Characterization of Novel Shape Memory Porous Poly(urethane-urea) Scaffold for Non-Union - Huang, Meina; Wang, Yuanliang; Luo, Yanfeng; Pan, Fusheng (Asian Journal of Chemistry, 2013)
A novel shape memory porous scaffold was prepared by copolymerization and emulsion copolymerization method. Initially, isocyanate terminated prepolymer was prepared from reaction of HO-terminated poly (lactide-co-p-dioxanone) with hexamethylene diisocyanate for 3 h at 70 75 ºC. Then the excess NCO reacted with butanediamine below 5 ºC, aiming to realize chain extension. During this process, the porogen NaCl/PVP was introduced. The emulsion was dried by vacuum and the dried materials were compressed to special shape and then salt leaching method was used to prepare porous scaffold. The pore structure and pore size were characterized by scanning electron microscopy and the porosity was measured with liquid substitution method and connectivity was measured by calculating the ratio of drip mass to time. Mechanical performance and shape memory property were also studied. These results denoted that pore size and porosity have significant influence on the mechanical and shape memory properties of shape memory poly(urethane-urea). However, the shape memory property is as high as 52 % 80 % and mechanical modulus is 100-350 MPa, similar to the natural bone, which is beneficial to treatment of the non-union.